2010
DOI: 10.1038/cmi.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized MHC class I chain-related protein A synergizes with IL-15 and soluble 4-1BB ligand to expand NK cells with high cytotoxicity ex vivo

Abstract: Major histocompatibility complex (MHC) class I chain-related protein A (MICA), which is a ligand for human NKG2D, is expressed by a variety of epithelial tumor cells and promotes the activation of natural killer (NK), CD8 1 and cd-T cells. Although ectopic expression of MICA on tumor cells elicits anti-tumor responses, soluble MICA downregulates the activities of lymphocytes. In this study, we showed that recombinant, immobilized MICA (iMICA) molecules coated on plastic wells weakly promote peripheral NK cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…Therefore, as our results demonstrate, anti-CD137 mAb stimulation enhances NK cell-DC crosstalk while also directly enhancing enhanced NK cell function. Our observation is consistent with additional mouse and human studies that report anti-CD137 enhancement of NK cell killing in both hematopoietic and solid tumors lacking expression of the CD137 ligand (33)(34)(35)(36). Rather, by first activating NK cells via CD16 and the Fc-FcγR interaction, surface expression of CD137 is induced and subsequently directly stimulated by administering the agonistic anti-CD137 mAb.…”
Section: Figuresupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, as our results demonstrate, anti-CD137 mAb stimulation enhances NK cell-DC crosstalk while also directly enhancing enhanced NK cell function. Our observation is consistent with additional mouse and human studies that report anti-CD137 enhancement of NK cell killing in both hematopoietic and solid tumors lacking expression of the CD137 ligand (33)(34)(35)(36). Rather, by first activating NK cells via CD16 and the Fc-FcγR interaction, surface expression of CD137 is induced and subsequently directly stimulated by administering the agonistic anti-CD137 mAb.…”
Section: Figuresupporting
confidence: 78%
“…Although CD137 stimulation has been shown to enhance NK cell function and proliferation in mice (33)(34)(35)(36), a recent study suggests that it may have opposite effects on human NK cells, leading to decreased function, including cytotoxicity (32). This discrepancy with our current results is likely due to differences in experimental conditions.…”
Section: Figurecontrasting
confidence: 57%
“…We have previously shown that the antilymphoma activity of anti-CD137 agonistic mAb monotherapy requires both CD8 T cells and NK cells (26). Although in the setting of acute myeloid leukemia, expression of CD137 ligand by the leukemic blasts has been shown to impair NK cell spontaneous cytotoxicity (27), additional mouse and human studies have observed enhanced NK cell function, including survival and spontaneous cytotoxicity against both hematopoietic and solid tumors (28)(29)(30)(31). We recently reported that rituximab-induced ADCC of CD20-expressing lymphoma could be augmented by anti-CD137 agonistic mAbs in multiple mouse models (32).…”
Section: Figurementioning
confidence: 99%
“…Several studies have reported findings that suggest administration of exogenous γc cytokines may augment the efficacy of mAb therapies that target TNFR receptors. Specifically, co-administration of IL-2 has been reported to enhance the anti-tumor immune responses of therapies targeting OX40 (CD134), GITR (CD357) and 4-1BB (CD137) [ 5 ],[ 6 ],[ 61 ],[ 62 ]. In this study, we observed that exposure to IL-2 led recently-activated CD8 + T cells to substantially increase their expression of 4-1BB, GITR, ICOS and OX40, at both the transcriptional and protein level.…”
Section: Discussionmentioning
confidence: 99%